ANALYSIS OF OPERATING SYSTEMS BLOCKCHAIN EQUITY CROWDFUNDING SCHEME ON ECOSYSTEMS RENEWABLE ENERGY BUSINESS IN INDONESIA - Angga Kusumah; Sofia Maulida; Pandu Adi Cakranegara (Jurnal Ekonomi, 2023)
The high initial investment value, which is comparable to fossil technology, is the key hurdle to the growth of renewable energy technology in Indonesia. The purpose of this project is to create a business model canvas for the utilization of renewable energy technology in conjunction with an Indonesian blockchain equity plan. This research is qualitative in nature since it uses direct interviews with respondents, direct observation of company activities, and secondary data from a range of sources to augment data from respondents. The researchers surveyed ten people from the blockchain and renewable energy industries. The analysis entails entering data from many sources into nine blocks of the Business Model Canvas (BMC), which then assesses the Strength, Weakness, Opportunity, and Threat of each block. It is envisaged that the findings of this study would be utilized to establish business strategies for organizations looking to adopt a blockchain equity crowdfunding scheme in the renewable energy company, as well as to offer investors and consumers’ confidence to invest in the renewable energy business ecosystem.